CH3NH3Pb(BF4)(3) and (C4H9NH3)2Pb(BF4)(4) family of 3D and 2D perovskites without and with iodide and bromide ions substitution - Nagane, Satyawan; Ogale, Satishchandra B. (Journal of Physical Chemistry Letters, 2016)
We report the synthesis of fully molecular ion (BF4 )-based organicinorganic hybrid perovskite CH3NH3Pb(BF4)(3), which is a wide band gap semiconductor, and the same can be easily tuned toward the visible by the incorporation of bromide or iodide ions in the crystal framework simply by changing lead precursors. We have also successfully transformed the distorted 3D molecular-ion-induced perovskite to 2D (C4H9NH3)(2)Pb(BF4)(4), (C4H9NH3)(2)PbBr(4x)(BF4)(x), and (C4H9NH3)(2)PbI(4x)(BF4)(x) perovskites that exhibit the optical absorption over the UV to visible region. The thin films of molecular-ion-containing 2D perovskites with Br and I anions show blue and green luminescence, respectively, under UV illumination.